2016
DOI: 10.1111/rda.12758
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus cell expansion and first polar body extrusion during in vitro oocyte maturation in relation to morphological and morphometric characteristics of the dromedary camel ovary

Abstract: The morphological and morphometric characteristics of the ovary are fundamental properties for in vitro oocyte maturation. Nuclear maturation, including first polar body (1PB) extrusion, cytoplasmic maturation and cumulus cell (CC) expansion are the criteria for in vitro maturation (IVM) of oocyte. This study was designed to determine the effect of morphological and morphometric features of the ovary on CC expansion and 1PB extrusion during IVM of oocyte in the adult female dromedary camel. The weight, volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Our results showed the same. In this study, The present studythe rates of camel oocyte in vitro maturation showed similar or higher capacity when compared with other studies, meaning that our camel IVM system was appropriate [22][23][24], and analysis revealed thea greater efficiency in obtaining enhanced maturation ratesmatured oocytes from of in vivo-matured oocytes compare to in vitro-sources [Table 1]. Indeed, we confirmed the enhanced capacities for cleavage and blastocyst stage formation of in vivo-matured oocytes.…”
Section: A C C E P T E Dsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results showed the same. In this study, The present studythe rates of camel oocyte in vitro maturation showed similar or higher capacity when compared with other studies, meaning that our camel IVM system was appropriate [22][23][24], and analysis revealed thea greater efficiency in obtaining enhanced maturation ratesmatured oocytes from of in vivo-matured oocytes compare to in vitro-sources [Table 1]. Indeed, we confirmed the enhanced capacities for cleavage and blastocyst stage formation of in vivo-matured oocytes.…”
Section: A C C E P T E Dsupporting
confidence: 85%
“…These results indicated that it is essential to choose an efficient oocyte maturation method to obtain stable results in the production of live births using SCNT. However, the oocyte maturation rate of camels was lower than that of other species after in vitro maturation, and studies were insufficient [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the low reproductive performance of camels is considered an important factor affecting camel populations. Employing in vitro embryo production (IVP) technologies is an efficient means of propagating genetically superior camels; however, compared to other livestock species, camel oocyte in vitro maturation (IVM) has been reported to be inefficient [1,2,3,4]. One of the main contributing factors is the limited availability of oocytes because the majority of the slaughtered animals are either old, culled for infertility, or very young and have not attained maturity; in addition, there is no standardized protocol for IVP in camels [3, 5].…”
mentioning
confidence: 99%
“…Cumulus oophorus (CCOs) são indispensáveis para as técnicas laboratoriais. A classificação da qualidade dos ovócitos pondera a aparência do citoplasma, que deve apresentar-se homogêneo e escuro, e as células do CCOs, que preferivelmente devem ser múltiplas (HEWITT e ENGLAND, 1997;LUVONI et al, 2005;MESBAH et al, 2016).…”
Section: Introductionunclassified